Gender-affirming care education in pharmacy: a scoping review protocol of practices in Canada and the USA - Rakhshan Kamran; Liam Jackman (BMJ Open)
Introduction Gender-affirming care refers to a range of social, psychological, medical and/or surgical interventions provided to affirm one’s gender. Pharmacists play a key role in gender-affirming care and are involved with choosing optimal treatments, monitoring progress/side-effects and providing education. However, it is currently unknown what gender-affirming care education is provided to pharmacy students and pharmacists according to information available in published literature. This is important to identify potential education gaps in pharmacy curricula and an understanding of the current state of gender-affirming care education in pharmacy.Methods and analysis This scoping review protocol follows guidance from Arksey and O’Malley and Levac and colleagues. The population, concept and context framework are used to specify the research question and subsequently the search strategy. Database searching will occur across four databases: Medline, Embase, APA PsycINFO and Scopus; with the search date ranging from inception to 1 January 2025. Eligible studies will include pharmacy students or pharmacists, and examine the presence of gender-affirming care pharmacy education in Canada and the USA. There are no restrictions to date. Article screening and extraction will occur independently and in duplicate. Educational interventions, gender-affirming care content and recommendations extracted from each article will be narratively synthesised. This work is undertaken with patients and public involvement.Ethics and dissemination Ethical approval is not required as this is a review of published studies and does not collect any human data. Results will be disseminated through a peer-reviewed publication and conference presentations.